A vocação memorialística de Isaías Alves : variantes (auto)biográficas - Quadros, Carla de (2014)
The memorialistic writing by Isaías Alves in Vida e obra do Barão de Macahubas (1942), Vocação pedagógica de Rui Barbosa (1959) and Matas do Sertão de Baixo (1967) has made a significant contribution to the discussion of stylistic boundaries, as well as to the analysis of rhetorical narrative of which he has made use, in a state of memorious narrator, intending to relate the memory report and the story writing. It is possible to observe the impressionist details of the narrator in his attempt to understand how Isaías Alves articulates his narrative production, considered memorialistic, reaching out to different text formats biography, autobiography, and memoir but always giving priority to the inscription of the self. This study has tried to map the stylistic boundaries among Literature, Social History, Social and Collective Memory, present in texts, considered hybrid, revisiting History, Literary Theory and concepts employed in genres such as (auto) biography, memoir and others in order to reconsider the paths which confirm the assertion that the presence of memory in Isaías Alves and his (auto) biographical variations adjust to an interdisciplinary dialogue that, although displaying a nostalgic slant, also commits to historiography, while signing a pact with himself. This suggests an intimate engagement marked by the place and position of the author/narrator. It is possible to observe in Isaías Alves an organic and positivist intellectual, who performed several public functions, without reaching the representativeness that others did, and which he rightly thought he deserved, in establishing relevant relations between history and memory through biographical and autobiographical reports. We defend, firstly, the initiative of placing the works mentioned here in the context of Brazilian literature, removing the classification wrappings mistakenly placed by scholars; reviewing the journey of a forgotten, or silenced, intellectual by virtue of his political choices, but admittedly a memorialist narrator who, mapping his sentimental impressions, could review the historic path of education in a tone which reminds us of the epics, in addition to the author s concerns about organizing files raising him to the category of guardian the memories of Recôncavo Sul Baiano and his own. To establish the analytical dialogue, theoreticians such as Philipe Lejeune (2008) Leonor Arfuch (2010), Francoise Dosse (2009), Diana Klinger (2012), Roland Barthes (1984), Luiz Costa Lima (1991) and Daniel Pécaut (1990), among others, have been examined.